The Role of Local Languages in Indonesian EFL Classrooms: A Systematic Literature Review - Erisyerico, Mimo Lalito; Artini, Luh Putu (IKIP Siliwangi, 2026)
In Indonesia, English is taught as a foreign language from elementary to university levels. The country has over 700 local languages, which bring both opportunities and challenges for teaching English. Local languages are often used to help students understand difficult concepts or materials. The local language does not seem to be considered to have a role in translanguaging to support the development of the second or foreign language learning. This study employed a systematic literature review method, analyzing sixteen research articles published between 2020 and 2025 that explore how local languages are used alongside Indonesian and English by teachers and students, as well as to identify the benefits and challenges. The results show that local languages are mostly used informally by teachers, for example, to let students plan ideas in their mother tongue, switch languages, give instructions, or explain difficult points. These practices help students participate more easily, understand lessons better, gain confidence, preserve their culture, and improve their language learning. Although there are some benefits, teachers still face problems like unclear policies, lack of materials, and limited preparation. Schools need clear rules, trained teachers, and good materials to use local languages well. Careful planning is also important for balancing the learning of English and culture.